Family Involvement with MD & A (Management Disclosure & Analysis) Readability Level - Tubagus Algan Roiston, Diarany Sucahyati, Iman Harymawan, (Jurnal Akuntansi, 2020)
This study aims to examine the relationship between family involvement and the readability level of the MD & A (Management Disclosure & Analysis) released by the company. This study uses 1795 final samples from firms listed on the Indonesia Stock Exchange in the period 2010-2018. We tested the research hypothesis using ordinary least square regression (OLS). This was done using the Stata software by adding a fixed effect for industry diversity in order to strengthen the study results. This study used two proxies of the family firm where there is the involvement of family members at the management level and related to the ownership of company shares. Both of these proxies show consistent results indicating that family firms tend to release less readable MD&As. Furthermore, the language differences were also tested in this study. Apart from the presentation of the MD&A in English or Indonesian, family firms still present reports with lower readability. This study provides a perspective to the authorities regarding the family firm's governance intended to help improve existing regulations.